Impact of preoperative body compositions on survival following resection of biliary tract cancer. Issue 4 (29th April 2019) - Yoon, Seung Bae; Choi, Moon Hyung; Song, Meiying; Lee, Ju Hyun; Lee, In Seok; Lee, Myung Ah.; Hong, Tae Ho; Jung, Eun Sun; Choi, Myung‐Gyu
Abstract: Background: Although surgical resection is the only potentially curative treatment for biliary tract cancer, the prognosis remains poor after a major operation such as pancreatoduodenectomy or hepatectomy. We aimed to investigate the impact of preoperative body compositions on long‐term survival of patients undergoing resection of biliary tract cancer. Methods: We analysed data of patients diagnosed with biliary tract cancer who underwent surgery from 2009 to 2015. Skeletal muscle area, skeletal muscle radiation attenuation, and visceral and subcutaneous adipose tissue areas were measured from the computed tomography images at L3 vertebral levels obtained before resection of cancer. Patients were divided into two groups based on the sex‐specific median values for each parameter, and long‐term survival was compared between the groups. Results: A total of 371 patients (women, 39.6%; mean age, 66.2 ± 9.6 years) were finally included in the analysis. Patients with low skeletal muscle index (SMI) had significantly shorter median survival than those with high SMI (29 vs. 39 months; P = 0.026). Patients with low skeletal muscle attenuation (SMA) also showed reduced survival compared with those with high SMA (median survival 25 vs. 60 months; P = 0.002). Combining these two factors, survival was highest in the high SMI/high SMA group (reference) and lowest in the low SMI/low SMA group (hazard ratio, 2.18; 95% confidence interval, 1.44–3.30). Visceral and subcutaneous adipose tissue areas were not associated with long‐term survival. Conclusions: Low SMI and low SMA on computed tomography scan have a negative impact on survival after resection of biliary tract cancer. They can be used in preoperative risk assessment to assist in treatment decision making.